The inflammasomes - Couillin, Isabelle; Pétrilli, Virginie; Martinon, Fabio (Progress in Inflammation Research, 2011)
The inflammasome was first described in 2002 as a molecular complex activating proinflammatory caspases and therefore regulating the maturation and biological activities of cytokines such as IL-1 and IL-18. This finding was substantiated by the identification of several mutations in the cias1 gene, encoding the human NLRP3 protein, responsible for several autoinflammatory disorders such as the Muckle Wells syndrome. Since, the interest for this complex has constantly increased and several inflammasome complexes with different specificities have been described. These inflammasomes sense a wide variety of pathogens and danger signals and are key players in the inflammatory response. With the contributions of leading international experts in the field, this book provides an extensive overview of the current knowledge of inflammasome biology and their role in health and disease.